The effect of the capital structure to the profitability of property companies in Malaysia / Mohd Hazril Yusof - Yusof, Mohd Hazril (2007)
The purpose of the study is to examine the of the capital structure to the profitability of the firm in the property industry in Malaysia. The investigation has been performed using panel data procedure for a sample of 72 Malaysian companies listed on the Bursa Malaysia Stock Exchange during 2003-2006. The variable that is tested in this paper is the debt to equity ratio and net profit margin. This study is applies Single Linear Regression method to analyze the relationship between two variables above. Findings indicate that debt is significantly inversely related to the net profit margin that as profitability of the firms.